Faktor-Faktor Yang Berhubungan Dengan Keluhan MUSCULOSKELETAL DISORDERS (MSDs) Pada Karyawan Bank X - Hardianto, Hardianto; Trisnawati, Elly; Rossa, Idjeriah (JUMANTIK (Jurnal Mahasiswa dan Peneliti Kesehatan), 2015)
Working on a computer with a long sitting position causes sense of fatigue in the skeletal muscles, especially the buffer such as the spine, thighs, and calves. Musculoskeletal disorders are divided into two, namely temporary and permanent complaints. WHO indicated that musculoskeletal disorders are considered as the major occupational illnesses (48%). This study aimed at discovering the factors related to MSDs among computer users at head office of Bank X, Pontianak City. Using analytical observation method and cross sectional design, as many as 84 employees participated in this study. They were selected by using purposive sampling technique. The data were statistically analyzed by using chi square test. The study revealed two findings. First, there were correlation of sex (p value=0,013;CC=0,307), relaxation (p value=0,000;CC=0,553), the use of hour break for working (p value=0,013;CC=0,348), exercise habit (p value=0,006;CC=0,327), extra working hours (p value=0,028;CC=0,281) length/ height and seat height compatibility (p value=0,005;CC=0,332), and MSDs complaints. Second there were no correlation of age (p value=0,399), working period (p value=1,000), IMT (p value=1,000), and MSDs complaint. However, arm ’s reach could not be tested as the data were homogeneous. From the findings, the company is encouraged to conduct health program and work place evaluation by providing office health clinic. This program is important to give health services to the employees such as disease treatment and to realize the ergonomic work station design.Key words: computers users, MSDs, Bank